COVID-19 and its relation to pregnancy and neonates: a systematic review - Gerson Aparecido Foratori-Junior; Victor Mosquim; Thais Marchini de Oliveira Valarelli; Maria Aparecida de Andrade Moreira Machado; Silvia Helena de Carvalho Sales-Peres
Abstract Objectives: this study systematically reviewed the literature in order to better understand the association among COVID-19, pregnancy and neonates. Methods: MEDLINE, EMBASE, Web of Science, BVS and SCOPUS were assessed, considering the terms: (covid 19 OR covid-19 OR novel coronavirus OR 2019 novel coronavirus OR 2019-nCoV OR sarscov 2 OR sars-cov-2 OR sarscov2 OR sars cov-2) AND (pregnancy OR pregnant OR pregnant women OR gestation OR gestational) AND (infant OR fetal OR neonatal). Thirty full-text were included (408 pregnant women, 11 non-pregnant women and 279 neonates). Results: fever (45.83%) and cough (31.61%) were the main symptoms of COVID-19 during the pregnancy. Low levels of lymphocytes (32.10%), elevated levels of C-reactive protein (32.35%); leukocytosis (29.41%); neutrophil (5.88%); and radiographic alterations on chest CT, x-ray or ultrasound (45.84%) were the main laboratorial findings. Cesarean delivery and preterm were registered in 239 and 49 cases, respectively. Ten neonates tested positive for SARS-CoV-2. Conclusion: when COVID-19 pneumonia affects women during pregnancy, the symptoms are similar to those experienced by non-pregnant women. In addition, there is still no plausible evidence suggesting vertical transmission of SARS-CoV-2 virus from mother to child.